Myocardial protection of S-nitroso-L-cysteine in diabetic cardiomyopathy mice - Peng, Lulu; Zhu, Mengying; Huo, Shengqi; Shi, Wei; Jiang, Tao; Peng, Dewei; Wang, Moran; Jiang, Yue; Guo, Junyi; Men, Lintong; Huang, Bingyu; Wang, Qian; et al. (Frontiers in Endocrinology, 2022)
Diabetic cardiomyopathy (DCM) is a severe complication of diabetes mellitus that is characterized by aberrant myocardial structure and function and is the primary cause of heart failure and death in diabetic patients. Endothelial dysfunction plays an essential role in diabetes and is associated with an increased risk of cardiovascular events, but its role in DCM is unclear. Previously, we showed that S-nitroso-L-cysteine(CSNO), an endogenous S-nitrosothiol derived from eNOS, inhibited the activity of protein tyrosine phosphatase 1B (PTP1B), a critical negative modulator of insulin signaling. In this study, we reported that CSNO treatment induced cellular insulin-dependent and insulin-independent glucose uptake. In addition, CSNO activated insulin signaling pathway and promoted GLUT4 membrane translocation. CSNO protected cardiomyocytes against high glucose-induced injury by ameliorating excessive autophagy activation, mitochondrial impairment and oxidative stress. Furthermore, nebulized CSNO improved cardiac function and myocardial fibrosis in diabetic mice. These results suggested a potential site for endothelial modulation of insulin sensitivity and energy metabolism in the development of DCM. Data from these studies will not only help us understand the mechanisms of DCM, but also provide new therapeutic options for treatment.